Variation in maternal provisioning by lactating Antarctic fur seals: response to experimental manipulation in pup demand - John Arnould; D Rawlins; IL Boyd; MA Hindell (2000)
Variation in maternal provisioning by lactating Antarctic fur seals: response to experimental manipulation in pup demand